Determining the persistence of Mycobacterium bovis bacille Calmette–Guerin Danish in select tissues of orally vaccinated feral swine (Sus scrofa ssp.). (February 2016) - Nol, Pauline; Robbe-Austerman, Suelee; Rhyan, Jack C.; McCollum, Matt P.; Triantis, Joni M.; Beltrán-Beck, Beatriz; Salman, Mo D.
Abstract: Mycobacterium bovis bacille Calmette–Guerin (BCG) is being considered for vaccination of feral swine ( Sus scrofa ssp. ). Since BCG is a live bacterium, evaluation of its safety and persistence in tissues is important. Fifteen feral swine received approximately 4.5 × 10 6 colony forming units of BCG Danish via oral bait. Four animals received bait without BCG. At 1, 3, 6, and 9 months post-vaccination, four vaccinates were euthanized. Non-vaccinates were euthanized at 9 months. Clinical signs were not noted in vaccinated pigs at any time. Tissues from all 20 pigs were culture-negative for mycobacteria. Based on our data, BCG is safe and appears not to persist in feral swine tissues after one month post-oral vaccination. However, further work must be performed at higher doses, and on a larger number of animals representing the target population, and further evaluation of persistence in tissues within the first month post-vaccination is needed. Highlights: BCG Danish did not persist in feral swine tissues 1–9 months after oral vaccination with 4.5 × 10 6  cfu. Oral BCG Danish did not induce clinical signs in feral swine in this study. Gross lesions were not noted in feral swine after oral vaccination with BCG Danish.